SOCIO ECONOMIC STATUS AND CONSTRAINTS FACED BY SHEPHERDS IN GUNTUR DISTRICT OF ANDHRA PRADESH (Indian Journal of Animal Production and Management, 2015)
A survey was conducted in Guntur district of Andhra Pradesh to collect the information regarding socio economic status of shepherds and constraints faced by them by using structured questionnaire. Survey covers the information regarding their land holding, literacy, their age groups, flock size and constraints in field level. Study revealed that the majorities (63.75%) of sheep farmers were of middle age and most of them were illiterate. About 90% of the respondents indicated that sheep farming was their main occupation of which 52.50% of farmers were landless and 37.92% of farmers were marginal farmers with average land holding Sireesha et al. of 5.1 to 7.5 acres of land. The major problems faced by the shepherds were lack of grazing lands, middleman hindrance in marketing of sheep and lack of organized meat markets.
Keywords: Socio-economic status; constraints; Guntur district; Andhra Pradesh